Comparative Study on Two Methods, Benson Relaxation Vs Premeditation, and Their Effect on Respiratory Rate and Pulse Rate of Patients Experiencing Coronary Angiography - R Emarian; F Ahmadi; N Hanifi; M Khani (Tehran University of Medical Sciences, 2005)
Background & Aim: One of the cause of anxiety for most patients is hospitalization. Once the patients are hospitalized for cardiac catheterization, the anxiety would be augmented. The anxiety raises body physiological and psychological activities such as: heart rate and respiratory rate. This research, as clinical trial study, has the objective to determine the influence of applying two methods of relaxation and premeditation on respiratory rate and pulse rate in hospitalized patients, experiencing coronary angiography, in heart and postangio wards of Shahid Beheshti Hospital in Zanjan, at 2003. Methods & Materials: 40 patients who were candidates for CA, has been studied, in regard to existing conditions and methods of sampling and random allocation to two groups of relaxation, and premedication. Data collection tool included demographic and disease related information sheet, as well as record sheets for respiratory rate and pulse rate at intervals of 8-12 and ½ hrs before, during and after the angiography. For relaxation group, the researcher would speak individually about the influence of relaxation, the day before angiography; then with the aid of client himself/herself, performed relaxation instances in a single bout, and eventually asked client to perform relaxation technique 2-3 times before going for angiography. In premedication group, patients received regular preangiographic medications including diazepam, chlorpheniramine, metoclopramid, and hydrocortisone. Respiratory rate and pulse rate were measured in both groups 8-12 and ½ hrs, before during and after CA. Afterward, resulted data were analyzed statistically by (SPSS) software for windows. Results: Pulse rate at 8-12 hours before, during and after the angiography showed no significant difference between two groups (p>0.05). Thus our research hypothesis that "alterations of respiratory rate and pulse rate in patients under coronary angiography, who get relaxation, are identical to those in premedicaton group", would be confirmed Conclusion: These results show that the premeditation method can be substituted by relaxation before practicing invasive procedures.